Autoimmune uveitis in Behçet's disease and Vogt‐Koyanagi‐Harada disease differ in tissue immune infiltration and T cell clonality - Hao Kang; Hongjian Sun; Yang Yang; Zewen K Tuong; Minglei Shu; Yunbo Wei; Yu Zhang; Di Yu; Yong Tao (Clinical & Translational Immunology, 2023)
Abstract Objectives Non‐infectious uveitis is often secondary to systemic autoimmune diseases, with Behçet's disease (BD) and Vogt‐Koyanagi‐Harada disease (VKHD) as the two most common causes. Uveitis in BD and VKHD can show similar clinical manifestations, but the underlying immunopathogenesis remains unclear. Methods To understand immune landscapes in inflammatory eye tissues, we performed single‐cell RNA paired with T cell receptor (TCR) sequencing of immune cell infiltrates in aqueous humour from six patients with BD (N = 3) and VKHD (N = 3) uveitis patients. Results Although T cells strongly infiltrated in both types of autoimmune uveitis, myeloid cells only significantly presented in BD uveitis but not in VKHD uveitis. Conversely, VKHD uveitis but not BD uveitis showed an overwhelming dominance by CD4+ T cells (> 80%) within the T cell population due to expansion of CD4+ T cell clusters with effector memory (Tem) phenotypes. Correspondingly, VKHD uveitis demonstrated a selective expansion of CD4+ T cell clones which were enriched in pro‐inflammatory Granzyme H+ CD4+ Tem cluster and showed TCR and Th1 pathway activation. In contrast, BD uveitis showed a preferential expansion of CD8+ T cell clones in pro‐inflammatory Granzyme H+ CD8+ Tem cluster, and pathway activation for cytoskeleton remodelling, cellular adhesion and cytotoxicity. Conclusion Single‐cell analyses of ocular tissues reveal distinct landscapes of immune cell infiltration and T‐cell clonal expansions between VKHD and BD uveitis. Preferential involvements of pro‐inflammatory CD4+ Th1 cells in VKHD and cytotoxic CD8+ T cells in BD suggest a difference in disease immunopathogenesis and can guide precision disease management.